PENGGUNAAN MEDIA MINI BOOK DALAM PEMBELAJARAN EKONOMI DIKELAS XI IIS MUHAMMADIYAH 2 PONTIANAK - Juliansyah, Rifqi; Buwono, Sri; Warneri, Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This research aims to knowing the difference of using media mini book with discourse method towards the learning outcome of student XI Muhammadiyah 2 Pontianak. The method was used experiment with the quasi experimental designe is non equivalent control group design. This research had become experiment class is student of XI IIS, therefore for the class control is XI MIA. The data was taken using instrument is essay which had validated the validity and reability. The result of this research shows there were differences of the average score between experiment and control class. The learning outcomes of students who had used mini book on economics subjects on national income material obtained an average post-test score of 62.83 and without using mini-books for 49.50. In the test the independent sample t test can be seen in the sig column (2-tailed), it is known that the sig. (2-tailed) value is 0.045 <0.05. It can be concluded that there is a difference between the use of mini-book media and without the use of mini-book media towards learning outcomes of students of class XI Muhammadiyah 2 Pontianak. Which means that H0 is rejected and Ha is accepted. From the calculation of the effect size, the result is 0.52 so it can be concluded that the effect size is classified as moderate. Keywords : Learning Outcomes, Mini Book